Effect of retinal defocus on basketball free throw shooting performance. (23rd March 2015) - Bulson, Ryan C; Ciuffreda, Kenneth J; Hayes, John; Ludlam, Diana P
<x xml:space="preserve">Abstract</x> Background Vision plays a critical role in athletic performance; however, previous studies have demonstrated that a variety of simulated athletic sensorimotor tasks can be surprisingly resilient to retinal defocus (blurred vision). The purpose of the present study was to extend this work to determine the effect of retinal defocus on overall basketball free throw performance, as well as for the factors gender, refractive error and experience. Methods Forty‐four young adult participants of both genders were recruited. They had a range of refractive errors and basketball experience. Each performed 20 standard basketball free throws under five lens defocus conditions in a randomised manner: plano, +1.50 D, +3.00 D, +4.50 D and +10.00 D. Results Overall, free throw performance was significantly reduced under the +10.00 D lens defocus condition only. Previous experience, but neither refractive error nor gender, yielded a statistically significant difference in performance. Conclusion Consistent with previous studies of complex sensorimotor tasks, basketball free throw performance was resilient to low and moderate levels of retinal defocus. Thus, for a relatively non‐dynamic motor task at a fixed far distance, such as the basketball free throw, precise visual clarity was not critical. Other factors such as motor memory may be important. However, in the dynamic athletic competitive environment it is likely that visual clarity plays a more critical role in one's performance level, at least for specific task demands.